1992
DOI: 10.1111/j.1600-0447.1992.tb03243.x
|View full text |Cite
|
Sign up to set email alerts
|

Do perceived parental rearing patterns influence social behaviour dimensions and disease severity in schizophrenia?

Abstract: In an explorative study, a clinical sample of 53 schizophrenic patients was examined. The EMBU inventory was used for measuring perceived parental rearing practices, the AfS for rating the quality of relationship to key relatives and the U-Scale for assessing social anxiety. The findings obtained were intercorrelated and compared with 3 selected parameters of disease severity: age at first hospitalization, number of treated episodes and length of hospital stay. The results suggest that the quality of contact w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The results of the present investigation crossvalidate the data obtained by Kahlil ( 13), who used the same assessment instrument in a sample of German schizophrenics. As in the case of the German sample, Swedish patients gave their parents a significantly higher score on the factor 'rejection' than did control subjects.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The results of the present investigation crossvalidate the data obtained by Kahlil ( 13), who used the same assessment instrument in a sample of German schizophrenics. As in the case of the German sample, Swedish patients gave their parents a significantly higher score on the factor 'rejection' than did control subjects.…”
Section: Discussionsupporting
confidence: 86%
“…The findings reported in the present study, which are consistent with those reported by other authors, have some degree of concurrent validity, and so should have some predictive validity as well. One prediction that can be made is that negative rearing experiences might contribute to the development of dysfunctional self-schemata in the offspring as suggested in the extended model of individual vulnerability proposed by Perris (21)(22)(23)(24), and that such experiences might be reflected by a poor level of social functioning, as suggested by Kahil ( 13). In order to verify these assumptions, a further investigation is currently in progress.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The information about premorbid personality traits was obtained from a single informant, their mothers. Information about paternal bonding behaviour was restricted to maternal bonding behaviour because mothers were most frequently selected as key relatives [29].…”
Section: Discussionmentioning
confidence: 99%